Preparation of Papers for IFAC Conferences & Symposia: Computer Vision-enabled Human-Cyber-Physical Workstation System towards Assembly 4.0. Issue 1 (2021) - Ling, Shiquan; Guo, Daqiang; Yan, Danqi; Huang, Futian; Zhang, Tongda; Leng, Yuquan; Rong, Yiming; Huang, George Q.
Abstract: Assembly systems are constantly upgrading towards Assembly 4.0 through penetration of emerging technologies in Industry 4.0. In this context, the human-cyber-physical system has been proposed recently and engineered to improve human abilities and capabilities to interact with machines in cyber-physical spaces dynamically. However, most existing frameworks are still not adaptive enough to integrate human in the loop due to the lack of full consideration of human limitations. This research proposes a human-cyber-physical workstation system (HCPWS) for assembly resources digitisation, interconnection and interaction through embedded CPS technologies. Computer vision is deployed for real-time dynamic information analysis within the workstation, and a prototype is built for HCPWS implementation and verification.